Characteristics of 7Be and 210Pb behavior in the atmosphere over Osaka, Japan, as well as the size distributions of the chemical compositions of aerosols attached by 7Be and 210Pb - Kosinarkaranun, Kanyanan; Pitakchaianan, Chonlada; Kumsut, Pantiwa; Hazama, Ryuta; Hamasaki, Tatsuhide; Rittirong, Anawat; Muramatsu, Hisakazu; Noithong, Pannipa (Radiation protection dosimetry, 2025)
Air pollution, particularly particulate matter 2.5, is a significant environmental concern in Southeast Asia, with adverse effects on human health. Major sources include vehicular emissions, industrial activities, agricultural burning, and transboundary haze. 7Be and 210Pb are tracers for studying aerosol behavior. Aerosol samples were collected using a high-volume air sampler, cascade impactor, and rainwater from the rooftop of Building No.16 (34.71° N, 135.64° E) at Osaka Sangyo University. Results showed that 7Be and 210Pb-carrying aerosols were mainly attached to aerosols smaller than 2 μm, peaking at 0.33-0.55 μm. This study reports the world's first simultaneous measurement of the activity size distribution of 7Be and 210Pb-carrying aerosols across the entire aerosol particle size range, including the smallest sizes. A strong correlation between 7Be and SO42- concentration and between 210Pb and SO42- concentration in summer 2020 suggests SO42-as their carrier. These findings improve understanding of atmospheric transport models and support air pollution mitigation strategies.